Desain Pembelajaran Membaca Kitab Kuning Model Dick and Carey di Madrasah Diniyyah Daruttaqwa Gresik - Moh. Alfian Hadist Saputra (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
One of Islamic education aims is shaping the personality of real individual Muslims in accordance with the values of Islamic religion. Islamic education empirically refers to Islamic educational institutions, one of which is madrasa diniyyah using yellow books as the main source of teaching. The writing of this article uses descriptive deductive and inductive analysis and uses some data from the results of several literatures, observations, interviews, and documentation. The analysis found how the learning design to read the yellow book designed in Madrasa Diniyyah of Daruttaqwa Gresik using the Dick and Carey learning design model. There are ten steps in the Dick and Carey model including 1) Identifying the learning objectives, 2) Carrying out an analysis of learning, 3) Analyzing learners and learning context, 4) Formulating performance goals, 5) Developing assessment instruments, 6) Developing learning strategies, 7) Developing learning materials, 8) Conducting formative evaluations, 9) Revising learning program drafts, and 10) Conducting summative evaluations. The learning program to read yellow books designed at Madrasa Diniyyah of Daruttaqwa Gresik uses all the steps of the Dick and Carey learning design model completely without a single step left.